2018
DOI: 10.1016/j.pvr.2018.05.003
|View full text |Cite
|
Sign up to set email alerts
|

HPV E6 oncoproteins and nucleic acids in neck lymph node fine needle aspirates and oral samples from patients with oropharyngeal squamous cell carcinoma

Abstract: Commercial assays measuring HPV E6 viral oncoproteins, E6/E7 mRNA or DNA were used to test neck lymph node fine needle aspirates (FNA) and oropharyngeal samples (saliva and oral swabs) from 59 Canadian patients with oropharyngeal squamous cell carcinomas (OPSCC). Overall agreements of p16 antigen staining of tumors to FNA tested for OncoE6™, Aptima HPV E6/E7 mRNA and cobas HPV DNA were 81.4% (k 0.53), 94.9% (k 0.83) and 91.1% (k 0.73) respectively. Using HPV presence in a subset of 25 tumors as the comparator,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
0
25
1
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to investigate the presence of both these biomarkers in a large group of cancer‐free individuals with a commercially available assay for HPV mRNA detection that has been fully validated for cervical cancer screening . So far, the Aptima HPV assay has been used only to detect HPV mRNA in the saliva of patients with OPC . Another study reported HPV mRNA detection in oral rinses but used homemade, nonstandardized methods and included only patients with HNC …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To the best of our knowledge, this is the first study to investigate the presence of both these biomarkers in a large group of cancer‐free individuals with a commercially available assay for HPV mRNA detection that has been fully validated for cervical cancer screening . So far, the Aptima HPV assay has been used only to detect HPV mRNA in the saliva of patients with OPC . Another study reported HPV mRNA detection in oral rinses but used homemade, nonstandardized methods and included only patients with HNC …”
Section: Discussionmentioning
confidence: 99%
“…22 So far, the Aptima HPV assay has been used only to detect HPV mRNA in the saliva of patients with OPC. 19 Another study reported HPV mRNA detection in oral rinses but used homemade, nonstandardized methods and included only patients with HNC. 17 In the current study, we first investigated the presence of HPV DNA, and we found that approximately 10% of the subjects were positive for high-risk types, with no significant differences between HIV-infected and uninfected subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another option for testing cytology aspirates for high‐risk HPV is molecular testing of aspirate material collected into a liquid‐based fixative in a fashion similar to that for cervicovaginal cytology. A variety of molecular assays, including Hybrid Capture 2, Cobas 4800, and Aptima, have been examined in the literature, with most studies showing correlations for HPV similar to what has been reported for p16 IHC . This strategy of using molecular HPV assays on liquid‐based cytology samples of neck aspirate material can confirm the presence of high‐risk HPV even for cystic metastases, for which cell block sections more frequently lack sufficient material for p16 IHC.…”
mentioning
confidence: 93%